The Primitivo Liver Cancer at the National Institute of Neoplastic Diseases - Seminario Varona, Mario (1961)
With advances in prophylaxis, eradication campaigns of infectious diseases and the reduction of infant mortality, has managed to increase the average human life; This factor coupled with the progress of civilization, has led to an increase in mortality from cancer. As an example, I can see in (44) box increased mortality between the periods 1952-1953 and 1956-1957 in various countries of the World.